Beetles (Coleoptera) new for the fauna of the Białowieża Forest including a species new for Poland - Plewa, Radosław; Jaworski, Tomasz; Tarwacki, Grzegorz; Sućko, Krzysztof; Konwerski, Szymon; Królik, Roman; Lasoń, Andrzej; Melke, Andrzej; Przewoźny, Marek; Ruta, Rafał; Szołtys, Henryk; Hilszczański, Jacek (Entomologica Fennica, 2019)
The paper presents new data on the occurrence of 69 beetle species collected in 2017 in the Białowieża Forest, NE Poland. The list contains representatives of 27 families: Anthribidae, Bostrichidae, Ciidae, Cleridae, Coccinellidae, Corylophidae, Cryptophagidae, Curculionidae, Dasytidae, Elateridae, Endomychidae, Eucnemidae, Histeridae, Laemophloeidae, Latridiidae, Leiodidae, Lycidae, Melandryidae, Mycetophagidae, Ptinidae, Ripiphoridae, Salpingidae, Staphylinidae, Tenebrionidae, Tetratomidae, Throscidae, and Zopheridae. The majority of the species represents saproxylic, i.e. dead wood-dependent, beetles. Biology and distribution of some rarely recorded species are briefly discussed. All species are reported for the first time from the Białowieża Forest and, furthermore, Corticaria crenicollis Mannerheim, 1844 (Latridiidae) is new for the fauna of Poland.